REGULATION OF THE FORMATION OF INCOME IN ENTERPRISES - Zurapov, Ali Utkirovich (Educational Research in Universal Sciences, 2023)
This article is aimed at recognizing income in accounting, correctly identifying profits and expenses, correctly identifying all expenses spent on recognizing income provided that it comes at a certain cost, and the need to apply the conditions for recognizing income associated with these processes based on the requirements of the principle of “relevance”: the inability to correctly calculate the element of accounting